The Relationship Between Diversification Strategy and Organizational Performance in Developed and Emerging Economy Contexts: Evidence from Turkey and Netherlands - YİĞİT, İHSAN; KARTALTEPE BEHRAM, NİHAL (Springer International Publishing, 2013)
The aim of this study is to determine whether there is a significant difference between types of diversification and performance values comparing Turkey and Netherlands. Diversification strategy and organizational performance relationship seems to differ across developed and developing countries. The data from 2007–2011 of 154 business groups in Netherlands and 125 business groups in Turkey were analyzed. ROA and ROS for organizational performance and Rumelt’s measure for diversification were used. According to the results, when organizational performance values are high for single businesses and unrelated diversification in Turkey, organizational performance is high for dominant businesses in Netherlands. © 2013, Eurasia Business and Economics Society.
Keywords: Diversification Strategy; Emerging Country; Organizational Performance